Approach to the meanings of work and family in health emergency - Riquelme-Segura, Leonor (2025)
At present, the transformations in society have permeated the institutions of work and family. Through a mixed methodology, we sought to know the meanings that 105 people who work for pay attribute to “Work” and “Family” in times of health emergency. Natural semantic networks were used to explore meanings and simple correspondence analysis to establish associations. The results obtained provided evidence about the meaning of work and family as social constructions, which are part of the individual and cultural identity of people, as well as the significant relationship of these constructs with gender and age.